Preliminary Study on Alternative Reflectors for LOTUS Reactor - Hong, Bui Thi; Mai Vu, Thanh; Hartanto, Donny (VNU Journal of Science: Mathematics - Physics, 2023)
LOTUS reactor - a compact lead-cooled fast reactor is currently being studied to generate 200 MWth of capacity and operate for 20 years without refueling for the floating nuclear power plant (FNPP) application. Therefore, it would be a big advantage to achieve a long operation without refueling. However, a small reactor usually has a higher neutron leakage, and a good neutron reflector is essential to maintain the neutron economy. The main objective is selecting potential reflectors materials for the LOTUS reactor using Monte Carlo code, Serpent. The various candidate reflector materials, including Al 2 O 3 , BeO, MgO, PbO, SiO 2 , and ZrO 2 are calculated from the neutronics characteristics to determine a good neutron reflector. In this work, we have investigated the parameters of neutronics characteristics, such as core neutron flux spectrum, evolution of k eff due to burn-up, power distribution, and lead coolant void reactivity with each reflector. From the comparison of those parameters, MgO material was found to be a good candidate for the relector of LOTUS reactor.